2016
DOI: 10.1111/jbg.12204
|View full text |Cite
|
Sign up to set email alerts
|

Selection against abdominal fat percentage may increase intramuscular fat content in broilers

Abstract: Excessive abdominal fat content (AFC) has negative impacts on feed efficiency and carcass quality. Unlike AFC, intramuscular fat content (IMFC) could be a favourable trait, which has a positive impact on meat quality. To meet consumers' needs, a long-term goal of broiler breeders is to decrease AFC and improve the IMFC simultaneously. The current study was designed to investigate the relationship between AFC and IMFC and to compare IMFC, including the pectoral major muscle fat content (PIMFC) and intramuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The extraordinary muscle development of modern broilers is going together with increased adipose tissue, predominantly fat adhered to mesentery, along the intestine from the pylorus to the colon (Wang et al, 2007; Leng et al, 2016). Published studies have identified several genes connected with adiposity in chickens, which may help to regulate the excessive accumulation of fat in the gastrointestinal tract (Bourneuf et al, 2006; Bornelöv et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The extraordinary muscle development of modern broilers is going together with increased adipose tissue, predominantly fat adhered to mesentery, along the intestine from the pylorus to the colon (Wang et al, 2007; Leng et al, 2016). Published studies have identified several genes connected with adiposity in chickens, which may help to regulate the excessive accumulation of fat in the gastrointestinal tract (Bourneuf et al, 2006; Bornelöv et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A higher growth rate induces larger fiber diameters and lower IMF deposition, which severely deteriorates the quality of meat [4, 5]. However, the overemphasis on selection for a rapid growth rate leads to excessive fat accumulation, especially AbF accumulation [6]. Excessive fat is often discarded as waste [68].…”
Section: Introductionmentioning
confidence: 99%
“…However, the overemphasis on selection for a rapid growth rate leads to excessive fat accumulation, especially AbF accumulation [6]. Excessive fat is often discarded as waste [68]. Reducing the levels of AbF and increasing the levels of IMF have therefore become a major breeding goals in the chickens industry [6, 9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations